The gendered affordances of Craigslist "new-in-town girls wanted" ads. (November 2019) - Schwartz, Becca; Neff, Gina
Sex-for-rent schemes have emerged on online sites as rental options. We analyzed 583 advertisements that were posted on Craigslist in London and Los Angeles and interviewed 34 women who were or had been in these arrangements. This research yielded four key tensions: (1) navigating innuendo (mis)interpretation versus preserving arranged ambiguity, (2) the guise of amateurism and romance versus persistent specificity, (3) calculated sacrifice versus narrative of a better life, and (4) consent versus consensual non-consent. Findings attest to the affordances online platforms offer by connecting geographically dispersed parties in a low risk, anonymous forum. Furthermore, present research joins discourses on the commercialization of intimacy and forms of precarious, gendered labor while asserting Internet features are pivotal in facilitating these arrangements. We propose gendered affordances to conceptualize how individual aspirational labor efforts, combined with platform affordances, commodify intimacy for sale on the moral marketplace.